Faith Matters: Towards a Public Missiology in the Midst of the Ecological Crisis - Fensham, Charles James (Toronto journal of theology, 2015)
The article examines public missiology in the light of the ecological crisis by situating public missiology in the larger context of public theology. It responds to the challenge of finding ways for Christian communities to act in the light of climate change. It notes developments in public theology, as well as the rise and dominance of a consumer capitalist economic story that frustrates action for the integrity of God's creation. It identifies public missiology with a locus in public theology. It distinguishes public missiology as the discipline that involves the church in active engagement. Drawing on the seminal thought of David Bosch and the work of Gregory Leffel in public Christian activism, the article argues for five dimensions in public missiology, which are inextricably intertwined. They include a public disposition of ongoing repentance, a humble and prayerful engagement within Christian community, an active engagement with the ecological crisis in the world (evangelism in community), a public telling of the story of the meaning of God's creation (proclamation), and a call to turn toward action for the integrity of creation (conversion). Out of the interplay of these dimensions, through theological reflection and careful consideration of critical social theory, a new public missiological story is to be woven that can capture the imagination of people, both of faith and no faith, to action for a healed creation.